Armenia : Recent Economic Developments and Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This paper reports economic developments in the Republic of Armenia during 1998-99. Prior to August 1998, real GDP growth was strong, inflation had declined to moderate levels, the current account deficit was declining, and the exchange rate was stable. The Russian crisis, however, hit Armenia hard. Exports, workers' remittances, and transfers fell sharply. This led to declining demand for output in industry, transportation, and services. In addition, Armenia suffered a decline in portfolio and direct foreign investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet